Plasticizer effect and electronic diffusive behavior of polyaniline-modified clay in polystyrene nanocomposites - Pinto C.P.* (2019)
© 2017 Society of Plastics EngineersMontmorillonite clay (MMT) was modified with polyaniline (Pani) and used to produce nanocomposites in a polystyrene (PS) matrix. MMT/Pani particles were evaluated by Infrared Spectroscopy (FT-IR), where groups of both MMT and Pani were found; and by XRD, where an increase in the interlamellar distance was detected, changes on the resistive electrical behavior of MMT to a diffusive one for MMT/Pani were identified by Electrochemical Impedance Spectroscopy (EIS). Nanocomposites of PS with MMT-Pani were produced by melt intercalation in the proportions of 1%, 3%, 5%, and 10%. They were characterized by Transmission Electron Microscopy (TEM), Differential Scanning Calorimetry (DSC), Thermogravimetry (TG), and EIS. Main results showed a decrease in the glass transition temperature and in the onset temperature according to the amount of MMT-Pani. Analyses by EIS demonstrated a capacitive behavior (polarization) for nanocomposites containing smaller amounts of MMT-Pani and diffusive behavior for the largest proportions, which were explained by a model of electronic diffusion in the Pani polymeric chain due to the chain intercalation observed by TEM in samples with higher concentration of MMT-Pani. Therefore, the results suggest that the addition of MMT-Pani alters some properties of the polystyrene matrix, changing its degradation and transition temperature, and its electrical behavior. POLYM. COMPOS., 40:37–45, 2019. © 2017 Society of Plastics Engineers.